LITERATUR REVIEW: PENERAPAN TERAPI NON FARMAKOLOGIS TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DENGAN ANEMIA - Dewi Candra Resmi; Fibrinika Tuta Setiani (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Background: Adolescence is a transition period from childhood to adulthood, usually occurs atthe age of 10 to 18 years. The problem that commonly occurs at this age is anemia, this can becaused in adolescence very much need iron to grow and develop besides that bleeding duringmenstruation is one of the factors causing it. Purpose: This study aims to examine theeffectiveness of the application of non-pharmacological therapies in the form of fruit andvegetables that are processed to increase hemoglobin levels in anemia cases experienced byadolescent girls. Methods: Literature review was conducted by collecting published research. The search wasperformed using the keywords Non pharmacological therapy, increased hemoglobin levels, adolescents, anemiaResults: The results of 5 journals with the same criteria as this study indicate that non- pharmacological therapy in the form of drinks or foods from fruits and vegetables has the benefitof increasing HB levels in cases of anemia experienced by adolescent girls. Conclusion: This non-pharmacological therapy in the form of fruit and vegetable drinks is veryeffective in increasing HB levels in cases of anemia experienced by adolescent girls. This stepwill be effective if consumed in a row for 7 to 10 days